Impact of rhabdomyolysis on outcomes of hospitalizations for heat stroke in the United States. Issue 5 (19th October 2020) - Thongprayoon, Charat; Petnak, Tananchai; Kanduri, Swetha R.; Kovvuru, Karthik; Cheungpasitporn, Wisit; Boonpheng, Boonphiphop; Chewcharat, Api; Bathini, Tarun; Medaura, Juan; Vallabhajosyula, Saraschandra; Kaewput, Wisit
ABSTRACT: Background: The objective of this study was to evaluate the predictors and associated outcomes of rhabdomyolysis in admitted patients for heat stroke in the United States. Methods: The National Inpatient Sample was utilized to identify hospitalized patients with a primary diagnosis of heat stroke from the years 2003–2014. Rhabdomyolysis was identified using hospital diagnosis code. We compared the clinical characteristics, in-hospital treatment, complications, outcomes, and resource utilization between patients with and without rhabdomyolysis. Results: A total of 3, 372 hospital admissions for heat stroke were studied. Of these, rhabdomyolysis occurred in 1049 (31%) admissions. The risk factors for rhabdomyolysis were age 20–39 years, male sex, African American race, history of alcohol drinking, whereas age ≥60 years, smoking, history of diabetes mellitus, and hypertension were associated with lower risk of rhabdomyolysis. Patients with rhabdomyolysis had greater requirements for mechanical ventilation, blood component transfusion, and renal replacement therapy. Rhabdomyolysis was significantly associated with increased risk of hyponatremia, hypernatremia, hyperkalemia, hypocalcemia, serum phosphorus and magnesium derangement, metabolic acidosis, sepsis, ventricular arrhythmia or cardiac arrest, renal failure, respiratory failure, liver failure, neurological failure, hematologic failure, and in-hospital mortality. Length of hospital stay and hospitalization cost were higher when rhabdomyolysis occurred during hospital stay. Conclusion: Rhabdomyolysis occurred in about one-third of hospitalized patients for heat stroke and was associated with increased morbidity, mortality, and resource utilization.